PENGARUH LINGKUNGAN KELUARGA, MOTIVASI DAN PERSEPSI MAHASISWA TENTANG PROFESI AKUNTAN PUBLIK TERHADAP MINAT MENJADI AKUNTAN PUBLIK PADA MAHASISWA PROGRAM STUDI AKUNTANSI UNIVERSITAS RIAU KEPULAUAN BATAM - Santoso, Cahyo Budi (MEASUREMENT : Jurnal Program Studi Akuntansi, 2014)
The purpose of this research was to determine the influence of the family environment, motivation and student’s perceptions about the public accounts profession with the partial and simultaneous to have the interests became public accountants on the accountancy students of the Economics Faculty, Riau Kepulauan University (UNRIKA) Batam. To know about that was used and distributed the questionnaire to all of students majoring in Accountancy of Economics Faculty, Riau Kepulauan University (UNRIKA) Batam (generation of 2011 and 2012), the provision has been following the lectured of Accounting Auditing I and Behavioral Accounting. The sampling method used is Slovin formula. The number of respondents is 144 respondents. In this research used multiple linear regression analysis method with consider to see the goodness of fit, it is the coefficient of determination, the value of the F statistic and t statistics. The results of this analysis indicate that there is a positive influence and simultaneously between family environment, motivation and student’s perceptions about the public accountantsprofession to be interest became the public accountant on the accountancy students of the Economics Faculty, Riau Kepulauan University (UNRIKA) Batam. This was shows the interest of students majoring in Accountancy of Economics Faculty, Riau Kepulauan University to the public accountants profession.